(untitled) (Training and Practice : Journal of Educational Sciences, 2019)
According to health indicators, we suffer a significant lag regarding diseases and mortality which can be avoidable with health services and public health interventions. Positive trends could be seen if healthy lifestyle has been promoted as early as possible. I am striving to summarize it in a form of synopsis in the manner of employing the related provisions of law on behalf of public health and public education. Education and pedagogy related to health issues appear to be inter-sectoral activities, which builds on the cooperation of interprofessional occupations. The exact definitions of functions appear in health related provisions of law including health development, protection of health (health education, health enlightenment) and prevention of disease while their fields are precisely defined in public education as well. The target group of education of healthy lifestyle includes educators, parents, while in institutions of education and pedagogy student-focused functions are present. As a whole, legal determination of educating healthy lifestyle is a variable multi-component task, which is also multidimensional, embedded into the daily routine, and based on cooperation within and amidst the sectors on behalf of public education and public health service.